Customized hydrogel substrates for serum-free expansion of functional hMSCs. (16th June 2020) - Le, Ngoc Nhi T.; Liu, Tianran Leona; Johnston, James; Krutty, John D.; Templeton, Kayla Marie; Harms, Victoria; Dias, Andrew; Le, Hau; Gopalan, Padma; Murphy, William L.
Abstract : Synthetic hydrogel arrays combined with a design of experiments approach identified hydrogel compositions for media-agnostic human mesenchymal stromal cell culture. Abstract : We describe a screening approach to identify customized substrates for serum-free human mesenchymal stromal cell (hMSC) culture. In particular, we combine a biomaterials screening approach with design of experiments (DOE) and multivariate analysis (MVA) to understand the effects of substrate stiffness, substrate adhesivity, and media composition on hMSC behavior in vitro . This approach enabled identification of poly(ethylene glycol)-based and integrin binding hydrogel substrate compositions that supported functional hMSC expansion in multiple serum-containing and serum-free media, as well as the expansion of MSCs from multiple, distinct sources. The identified substrates were compatible with standard thaw, seed, and harvest protocols. Finally, we used MVA on the screening data to reveal the importance of serum and substrate stiffness on hMSC expansion, highlighting the need for customized cell culture substrates in optimal hMSC biomanufacturing processes.